Improving literacy in Kapencar Village, Wonosobo, through the KKN Unsoed program - Ridlwan Kamaluddin; Loliana Riski; Lutfi Ngatifah; Alya Sania Laili; Amanda Aura Putri; Leonardo Leonardo; Kautsar Ikraam Esalka (Universitas Pendidikan Indonesia, 2026)
Such literacy practices are often unpopular with students, especially children, because they are considered monotonous and uninteresting. Universitas Jenderal Soedirman implemented the Thematic Community Service Program (Kuliah Kerja Nyata or KKN) on Literacy in Kapencar Village to improve reading interest and literacy skills among the community, especially for children. The primary issue facing this village is a low literacy culture, mainly due to a lack of awareness about the importance of literacy. The program employed a participatory approach, utilizing the Participatory Action Research (PAR) model, which involved students, teachers, library managers, and village officials. Conducted over 35 days, the program engaged 435 kindergarten and elementary school students through five core activities: literacy visits, read-aloud sessions, book review exercises, story writing exercises based on reading materials, and empowering village libraries. The results indicated improvements in basic literacy skills, writing creativity, and students’ confidence in expressing ideas. Moreover, the village library became more actively visited by children for reading and borrowing books. Challenges included limited book collections, varying student abilities, and the short duration of activities. Nevertheless, the program successfully fostered a supportive literacy environment in Kapencar Village. For sustainability, it is recommended to establish literacy groups, strengthen collaboration with schools and libraries, and involve parents in encouraging reading habits at home. Abstrak Praktik literasi seringkali kurang diminati oleh murid, khususnya anak-anak, karena dianggap monoton dan kurang menarik. Universitas Jenderal Soedirman melaksanakan Program Kuliah Kerja Nyata (KKN) Tematik Literasi di Desa Kapencar, untuk meningkatkan minat baca dan keterampilan literasi masyarakat, khususnya bagi anak-anak. Permasalahan utama yang dihadapi desa ini adalah rendahnya budaya literasi akibat kurangnya kesadaran terhadap literasi. Metode pelaksanaan menggunakan pendekatan partisipatif melalui model Participatory Action Research (PAR), dengan melibatkan murid, guru, pengelola perpustakaan, dan perangkat desa. Selama 35 hari, program diikuti oleh 435 murid TK dan SD melalui lima kegiatan inti, yaitu kunjungan literasi, membaca nyaring, mengulas buku, menulis cerita berbasis bacaan, dan pemberdayaan perpustakaan desa. Hasil kegiatan menunjukkan adanya peningkatan keterampilan literasi dasar, kreativitas menulis, serta kepercayaan diri murid dalam mengekspresikan gagasan. Selain itu, perpustakaan desa mulai aktif dikunjungi anak-anak untuk membaca dan meminjam buku. Kendala yang dihadapi meliputi keterbatasan koleksi buku, perbedaan kemampuan murid, serta waktu pelaksanaan yang singkat. Meskipun demikian, program ini berhasil membangun lingkungan literasi yang lebih suportif. Untuk keberlanjutan, disarankan pembentukan kelompok literasi desa, kolaborasi rutin dengan sekolah dan perpustakaan, serta keterlibatan orang tua dalam membiasakan anak membaca di rumah. Kata Kunci: kuliah kerja nyata; membaca buku; menulis cerita; pengembangan literasi